Ferroptosis and its current progress in gastric cancer - Yue, Zhenqi; Yuan, Yiwu; Zhou, Qi; Sheng, Jie; Xin, Lin (Frontiers in Cell and Developmental Biology, 2024)
Gastric Cancer(GC) is a prevalent malignancy within the digestive tract, ranking as the fifth most common malignant tumor worldwide. It is characterized by clinical features such as a tendency for metastasis and an unfavorable prognosis. Ferroptosis, a recently identified form of cell death, represents a novel mode of cellular demise that diverges from the traditional concepts of necrosis and apoptosis. Numerous studies have found that ferroptosis plays a significant role in the proliferation, metastasis, drug resistance, and microenvironment regulation within GC. This review summarizes the mechanism of ferroptosis and its role in the occurrence and development of GC cells. It provides examples demonstrating how various anti-tumor drugs can induce ferroptosis in GC cells. Additionally, it summarizes the potential application value of ferroptosis in the future treatment of GC.